Literature Review Evaluasi Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) Dengan Metode Hot-Fit - Lina Khasanah; Farhan Fajar Imani (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2022)
Introduction . Entering the digital era, technological developments are increasingly rapid in various fields, one of which is in the health sector. Information systems have a big impact on organizational success. Hospitals as complex organizations need complete information technology support, accurate and consistent with the hospital's needs and objectives to support its operation to be effective and efficient. An evaluation of a information system is a real effort to know the true condition of an information system arrangement. With this evaluation, the achievements of the implementation of an information system can be known and further actions can be planned to improve the performance of its application. The purpose of this study was to describe the evaluation of hospital management information systems (SIMRS) using the hot-fit method. Methode The method used in this research is a literature review. The object of this research is the journal for the last 5 years. Data collection used is secondary data. Data analysis was carried out in a descriptive qualitative manner with literature review techniques, namely looking for similarities, inequalities, views, comparisons and summaries of several studies. Results The results of 5 literature journals shows that the implementation of SIMRS has not run smoothly, this is due to the fact that there are still obstacles from the human aspect of the number of officers who do not understand and understand in using SIMRS due to the absence of training, from the organizational aspect the lack of support, supervision, and evaluation from the management, and from the aspect of network quality technology. not good and the quality of information and services is not optimal. Conclusion SIMRS implementation has not run optimally due to the discovery of several obstacles in the three factors, namely Human, Organization and Technology. It is hoped that related parties pay more attention and prepare everything related to SIMRS properly.